Impact of Canadian Armed Forces Veterans' Mental Health Problems on the Family During the Military to Civilian Transition. (2nd April 2020) - Cramm, Heidi; Norris, Deborah; Schwartz, Kelly Dean; Tam-Seto, Linna; Williams, Ashley; Mahar, Alyson
Abstract: Military to civilian transition can significantly affect veterans' lives. This study aimed to increase understanding of how veteran mental health problems impact the family during the transition to civilian life. We used a sequential multiple qualitative design. Twenty-six family members of veterans with mental health problems completed individual interviews and 9 participated in 3 focus groups. Veteran's mental health problem(s) created multifaceted and pervasive changes in family structure, roles, and routines, and these changes created negative mental health and well-being impacts for family members. Transition may compound stressors related to mental health, with significant consequences for family systems.